Empowerment of Micro, Small and Medium Enterprises in Increasing Sales Turnover Through the Ramadhan Market in Brodot Village, Bandarkedungmulyo District - Yayat Dimyati; Ilyas Nurul Azzam; Sutrisno; M. Fahmi; Rima Anjani (Ihsanniat: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service aims to empower Micro, Small, and Medium Enterprises (MSMEs) in Brodot Village to increase sales turnover through optimizing the Ramadhan Market activities. MSMEs are an important sector in the local economy that has great potential but often faces various challenges, such as limited market access, minimal product innovation, and lack of effective marketing strategies. This activity was carried out by a team from STAI At-Tahdzib in collaboration with the Brodot Village government. The activity methods include field observation, training, direct assistance, and ongoing evaluation. Initial observations showed that the majority of MSMEs did not have adequate understanding of digital marketing and attractive product packaging. In the training, participants were given materials about promotional techniques, the use of social media, simple financial management, and product branding. The Ramadhan Market was used as a direct practice medium to sell their products openly to the public. MSMEs were facilitated with tents, promotional banners, and social media as promotional tools. The results of the activity showed a significant increase in sales turnover, especially for snack and pastry products. In addition to financial improvements, this activity also increased the knowledge and confidence of business actors in developing their products. Participants began to actively utilize online platforms such as WhatsApp, Instagram, and Facebook for promotion. Several MSMEs began to package products with more attractive labels and designs. This activity also encouraged collaboration between business actors and created a stronger local business network. During the activity, community enthusiasm was very high. The Ramadan Market became a seasonal economic center that had a positive impact on the village economy. Students involved also gained practical experience in the community empowerment process based on devotion.